PENINGKATKAN HASIL BELAJAR SENI BUDAYA MELALUI PENGGUNAAN METODE DEMONSTRASI PADA SISWA SMP - Rusmauli Hutahayan; Tirawati Bakara (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to improve the learning outcomes of art and culture students of class VII-1 SMP Negeri 2 Deli Tua for the 2017/2018 academic year through the use of the demonstration method. This research is a classroom action research which consists of four stages, namely planning, implementation, observation and reflection. This classroom action research was carried out in two cycles, each cycle consisting of two meetings. This research was conducted at SMP Negeri 2 Sunggal. The subjects in this study were students of class VIII-1, totaling 32 people. The data collection tool used is an observation sheet designed to see student learning activities and test learning outcomes. The result of this research is that there is an increase in student learning outcomes in each cycle, namely in the first cycle with an average of 67.81 and in the second cycle it increases to 84.30. In the first cycle there was an increase in student activity, namely 32% included in the low category. Furthermore, in the second cycle there was an increase of 76% and was included in the high category.